Solubility and Antimicrobial Activity of Functional Hard Candy from Trigonas Honey (Trigona itama) and Microencapsulation of Patchouli Oil (Pogostemon cablin Benth) Based Essential Oils - Juliani, Juliani; Irmayanti, Irmayanti; AK, M. Daud (Jurnal Medika Veterinaria, 2024)
Candy is a group of snacks high in sugar content, so it has an impact on oral problems such as tooth decay. The use of natural flavors in the form of essential oils in candy which have antimicrobial activity has several obstacles, including not being easily dissolved. Therefore, essential oils need to be formulated to be solvable. One of the ways is by encapsulation using water-soluble coatings such as gum arabic, inulin and maltodextrin using a spray dryer. Product analysis was carried out for solubility tests and growth inhibition tests for Candida albicans and Streptococcus mutans. This research was conducted using two parameters, first parameter was coating materials consisting of 3 levels, namely; gumarabic (A), inulin (B) dan maltodextrin (C) . The second factor is the concentration of patchouli oil based essential oils which consists of 3 levels, namely; 0.01 g (K1), 0,05 g (K2) dan 0,025 g (K3). The results showed that the solubility of essential oils with three coating materials ranged from 44.77% -44.97%. From the analysis of variance, it can be concluded that differences in coating materials, essential oil concentrations and their interactions have a significant effect (P0.05) on inhibiting the growth of Candida albicans and Streptococcus mutans. The best treatment was obtained from the AK1 sample with inhibition against Candida albicans and Streptococcus mutans of 8.6 2.6 and 10 1.6 mm, respectively.